Advances in production of high-value lipids by oleaginous yeasts. (2nd January 2022) - Szczepańska, Patrycja; Hapeta, Piotr; Lazar, Zbigniew
Abstract: The global market for high-value fatty acids production, mainly omega-3/6, hydroxy fatty-acids, waxes and their derivatives, has seen strong development in the last decade. The reason for this growth was the increasing utilization of these lipids as significant ingredients for cosmetics, food and the oleochemical industries. The large demand for these compounds resulted in a greater scientific interest in research focused on alternative sources of oil production - among which microorganisms attracted the most attention. Microbial oil production offers the possibility to engineer the pathways and store lipids enriched with the desired fatty acids. Moreover, costly chemical steps are avoided and direct commercial use of these fatty acids is available. Among all microorganisms, the oleaginous yeasts have become the most promising hosts for lipid production - their efficient lipogenesis, ability to use various (often highly affordable) carbon sources, feasible large-scale cultivations and wide range of available genetic engineering tools turns them into powerful micro-factories. This review is an in-depth description of the recent developments in the engineering of the lipid biosynthetic pathway with oleaginous yeasts. The different classes of valuable lipid compounds with their derivatives are described and their importance for human health and industry is presented. The emphasis is also placed on the optimization of culture conditions in order to improve the yield and titer of these valuable compounds. Furthermore, the important economic aspects of the current microbial oil production are discussed.